Comorbidities of Migraine - Wang, Shuu-Jiun; Fuh, Jong-Ling; Chen, Ping-Kun (Frontiers in Neurology, 2010)
Migraine is a common neurological disorder and can cause severely disabling during attacks. The highest prevalence occurs between the ages of 25 and 55 years, potentially the most productive period of life. Migraine leads to a burden not only to the individual, but also to the family and society. Prior studies have found migraine occurs with some illness at a greater than coincidental rate than is seen in the general population. These occurrences are called “comorbidity”, which means that these disorders are interrelated with migraine. To delineate migraine comorbidity is important because it can help improve treatment strategies and understand the possible pathophysiology of migraine. The comorbid illnesses in patients with migraine include stroke, sub-clinical vascular brain lesions, coronary heart disease, hypertension, patent foramen ovale, psychiatric diseases (depression, anxiety, bipolar disorder, panic disorder, and suicide), restless legs syndrome, epilepsy, and asthma. In this paper, we review the existing epidemiological and hospital based studies and illustrate the connections between these illness and migraine.